2020
DOI: 10.3389/fcell.2020.00290
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-381-3p Functions as a Dual Suppressor of Apoptosis and Necroptosis and Promotes Proliferation of Renal Cancer Cells

Abstract: Renal cell carcinoma (RCC) is the most common type of kidney cancer. It has a poor prognosis, with approximately 20-30% of patients developing recurrent and/or metastatic diseases that is relatively high resistant to conventional therapy. Resisting cell death is a hallmark of cancer cells. Apoptosis is a form of programmed cell death mediated by the activation of caspases. Necroptosis is a form of regulated necrosis that relies on the activation of receptor-interacting protein kinase 1 (RIPK1), RIPK3 and mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…In the present study, survival analysis using the KM Plotter revealed that the low transcription levels of caspase-4 and 9 are related to low relapse-free survival in BCa. This study was consistent with earlier investigations in which researchers concluded that the caspase family is operated as new prognostic indicators in various cancers, including breast [ 79 ], gastric [ 80 ], ovary [ 81 ], and renal [ 82 ]. TNM plot analysis showed that the expression of caspase-4 and GSDME was significantly inhibited in clinical tissues in normal (113), tumor (1097), and metastatic (07) states, which was consistent with the earlier investigation [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, survival analysis using the KM Plotter revealed that the low transcription levels of caspase-4 and 9 are related to low relapse-free survival in BCa. This study was consistent with earlier investigations in which researchers concluded that the caspase family is operated as new prognostic indicators in various cancers, including breast [ 79 ], gastric [ 80 ], ovary [ 81 ], and renal [ 82 ]. TNM plot analysis showed that the expression of caspase-4 and GSDME was significantly inhibited in clinical tissues in normal (113), tumor (1097), and metastatic (07) states, which was consistent with the earlier investigation [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…miR-381-3p also functions as a tumour suppressor in non-small-cell lung cancer (34), oral squamous cell carcinoma (35), breast cancer (36), and cervical cancer (37). However, Zhao et al (38) demonstrated that miR-381-3p can promote renal cell carcinoma by inhibiting apoptosis and necrosis. However, miR-381-3p has not been reported in CRC-related research.…”
Section: Discussionmentioning
confidence: 99%
“…Bone regeneration is the key to fracture healing, which involves the proliferation, apoptosis and differentiation of osteoblasts ( 20 ), implying that methods that regulate osteoblastic activity may assist fracture healing. miRNAs have important regulatory effects on various cellular processes, such as cell proliferation, migration, invasion, differentiation and apoptosis ( 21 ). Emerging studies have focused on deregulated miRNAs during fracture healing, which are expected to promote the development of novel strategies to accelerate healing by improving osteoblastic viability.…”
Section: Discussionmentioning
confidence: 99%